2010
DOI: 10.1002/app.32313
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the spontaneous thermal homopolymerization of methyl andn‐butyl acrylate

Abstract: This article presents an experimental study of the spontaneous thermal homopolymerization of methyl acrylate (MA) and n-butyl acrylate (nBA) in the absence of any known added initiators at 120 and 140 C in a batch reactor. The effects of the solvent type, oxygen level, and reaction temperature on the monomer conversion and polymer average molecular weights were investigated. Three solvents, dimethyl sulfoxide (DMSO; polar, aprotic), cyclohexanone (polar, aprotic), and xylene (nonpolar) were used. The spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Grady et al and Quan et al reported reproducible monomer conversions of 70–90% in homopolymerization and copolymerization of a class of alkyl acrylates and methacrylates at 120–200°C in the absence of any conventional thermal initiators. Density functional theory (DFT) studies combined with experimental mass spectrometric analysis revealed that the Flory mechanism is responsible for the monomer self‐initiation at high temperatures. It was shown that two types of monoradicals (shown in Chart ), monomeric monoradical (MMR), and dimeric monoradical (DMR), are the initiating species in the self‐initiated homopolymerization of alkyl acrylates and methacrylates …”
Section: Introductionmentioning
confidence: 99%
“…Grady et al and Quan et al reported reproducible monomer conversions of 70–90% in homopolymerization and copolymerization of a class of alkyl acrylates and methacrylates at 120–200°C in the absence of any conventional thermal initiators. Density functional theory (DFT) studies combined with experimental mass spectrometric analysis revealed that the Flory mechanism is responsible for the monomer self‐initiation at high temperatures. It was shown that two types of monoradicals (shown in Chart ), monomeric monoradical (MMR), and dimeric monoradical (DMR), are the initiating species in the self‐initiated homopolymerization of alkyl acrylates and methacrylates …”
Section: Introductionmentioning
confidence: 99%
“…All of this suggests a dead macroinitiator. The reasons for this are not entirely clear at this point but it is possible that the second batch was polymerized strictly thermally at high temperatures, which has been observed in acrylate polymerizations …”
Section: Resultsmentioning
confidence: 99%
“…Studies using electron spray ionization-Fourier transform mass spectrometry (ESI-FTMS), nuclear magnetic resonance (NMR) spectroscopy, and macroscopic mechanistic modeling did not identify the initiating species or the mechanism of initiation in the spontaneous thermal polymerization [7,9]. However, quantum chemical calculations [10][11][12][13] together with matrix-assisted laser desorption ionization (MALDI) [14] showed that monomer self-initiation is one of the likely mechanisms of initiation in spontaneous thermal polymerization of alkyl acrylates.…”
Section: Introductionmentioning
confidence: 99%